A practical guide to the New European Bauhaus self-assessment method and tool - Gkatzogias, Konstantinos; Lourenço, Paulo B.; Maloutas, Thomas; Romano, Elvira; Santamouris, Matthaios; Negro, Paolo; Widera, Barbara; Ansaloni, Francesca; Balaras, Costas; Katurić, Ivana; Kolokotsa, Dionysia; Rossetto,Tiziana; et al. (European Commission, 2025)
This handbook provides a complete guide to the New European Bauhaus (NEB) self-assessment method, designed to promote the three NEB dimensions, namely sustainability, beauty, and inclusiveness, in the built environment of Europe and beyond. The handbook comes together with an online tool allowing to evaluate the performance of projects and support their improvement. The online tool is seen as the basis to establish a dialogue between all involved stakeholders, and the grounds for defining minimum performance levels within the NEB framework.
Advanced targets and indices are proposed to help professionals assess all aspects of the three NEB dimensions in buildings and living spaces, promote sustainable economic and financial activities, overcome local constraints, and improve the quality of life of the European citizens, indoors and outdoors, through a built environment designed to be affordable, aesthetically appealing, healthy, comfortable, and accessible for everyone, also addressing safety, functionality under hazards, adaptation to new functions. Acknowledging the complexity of a comprehensive evaluation, and understanding the variability of metrics associated with the three NEB dimensions across different project types, scales, and geographical regions, the self-assessment method is structured hierarchically to provide feedback with three interconnected assessment levels: indicator, key performance indicator, and dimension. Specifically, the method defines three spatial scales, i.e. building, neighbourhood, and urban, and delineates two project types, i.e. newbuild and renovation. Supporting the self-assessment process, the online tool aims to facilitate the user and simplify the evaluation process while upholding the method integrity and effectiveness. This handbook offers a thorough guidance on the New European Bauhaus self-assessment method and its underlying principles. It covers assessment targets, indicators, key performance indicators, evaluation methods, and measurement units. Additionally, the handbook includes illustrative examples, empowering the interested users with the knowledge necessary to perform the evaluation effectively.
The handbook primarily targets professionals engaged in both the delivery phase (design, construction, and commissioning) and the operational phase (operations and maintenance). Project managers, architects, engineers, and consultants are anticipated to play an active role in gathering and generating the information needed for the self-assessment. However, various stakeholders throughout the entire building lifecycle and supply chains are also expected to participate, benefit from, and be influenced by the assessment, including product manufacturers, main and specialist contractors, policymakers, building users and the local community members directly impacted by the project outcomes. The method is not intended to foster competition or reward high-scoring projects; rather, its purpose is to drive continuous improvement in the built environment quality and align projects with the NEB objectives. Whereas users are expected to aim at the highest performance in the self-assessment, the decision of focusing more on some performance indicators rather than others is finally left each user. To emphasise the significance of a balanced performance across all three dimensions of projects, the possibility of obtaining a global performance combining the three NEB dimension scores was intentionally excluded.